Analysis of the effectiveness of the implementation of the e-kinerja system as a tool for monitoring employee’s performance in the Technical Implementation Unit of Regional (UPTD) labor inspection in region I Bogor - Widiyanto, Edi; Islah, Khikmatul (Priviet Social Sciences Journal, 2026)
In frame increase performance apparatus and competence source Power man as well as increase supervision to performance employees at the Technical Implementation Unit of Regional (UPTD) Labor Inspection Region I Bogor, then Provincial Regional Government West Java implements a web-based system called e-kinerja. The effectiveness of the e-kinerja system is very influential in the effectiveness of employees’ performance at the UPTD Labor Inspection Region I Bogor. This is to determine the results of performance from an employee, whether increased or decreased. Low-quality performance from employees can be caused by several aspects, among them is that the main task points and functions in existing jobs are not yet optimally executed, and the lack of accuracy time in e-kinerja implementation as well as lack of supervision to performance employee. The purpose of this study is to determine the effectiveness of the e-kinerja system as a tool for supervising performance at the UPTD Labor Inspection Region I Bogor, which refers to the theory of Budiani and uses the following variables: accuracy targets, programs, program socialization, program objectives, and program monitoring. The methods used in this study are descriptive with a qualitative approach using observation, interviews, and documentation as data sources. The research results show that the implementation and application of the e-kinerja system is successful as a tool that plays a role in supervising employees’ performance at the Labor Inspection UPTD Region I Bogor.